Coupled thermo-hydro-mechanical-chemical processes with reactive dissolution by non-equilibrium thermodynamics. (December 2022) - Ma, Yue; Ge, Shangqi; Yang, He; Chen, Xiaohui
Abstract: The Clausius-Duhem Inequality has been widely adopted to model the coupled Thermo-Hydro-Mechanical-Chemical processes. However, this paper points out that when modelling a reacting system, the Clausius-Duhem Inequality may hide the reaction mechanism and reaction type if the reaction changes the solid, and it may generate imprecise constitutive result if the reaction occurs within the fluid without changing the solid. To overcome these challenges, this paper proposed a novel non-equilibrium thermodynamics approach to model the multiphysics coupling processes with reactive dissolution. The new approach focuses on the Helmholtz free energy change in a dissolution process by quantifying the entropy production with the knowledge from non-equilibrium thermodynamics. A new concept, solid affinity, is introduced to give a better description of Helmholtz free energy change due to reactive dissolution. The coupled Thermo-Hydro-Mechanical-Chemical equations with reactive dissolution are derived by this approach. A numerical simulation is presented to show the role of quartz dissolution.